2007
DOI: 10.1007/s00228-007-0442-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folic acid supplementation on the pharmacokinetics and pharmacodynamics of oral methotrexate during the remission-induction period of treatment for moderate-to-severe plaque psoriasis

Abstract: The antipsoriatic effect of MTX during the remission-induction phase of treatment is influenced by folate status and may be significantly less if combined treatment with FA is used, irrespective of pre-treatment folate levels. The individual tailoring of MTX dosing needs further attention because the mean percent PASI improvement from baseline was 83% and the inter-patient variability in response was low after 16 weeks of monotherapy with MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 22 publications
1
58
2
3
Order By: Relevance
“…Thus, high concentrations of intracellular folates may result in a decrease in MTX polyglutamation (37,38). In patients with psoriasis, use of folic acid 20 mg per week concomitantly with MTX resulted in lower RBC MTXGlu n concentrations compared with those found in patients taking MTX alone, although the difference did not reach statistical significance (39). While we observed a trend toward lower RBC MTXGlu 1 concentrations with higher RBC folate levels, this reached statistical significance in the multivariate analysis only.…”
Section: Discussioncontrasting
confidence: 67%
“…Thus, high concentrations of intracellular folates may result in a decrease in MTX polyglutamation (37,38). In patients with psoriasis, use of folic acid 20 mg per week concomitantly with MTX resulted in lower RBC MTXGlu n concentrations compared with those found in patients taking MTX alone, although the difference did not reach statistical significance (39). While we observed a trend toward lower RBC MTXGlu 1 concentrations with higher RBC folate levels, this reached statistical significance in the multivariate analysis only.…”
Section: Discussioncontrasting
confidence: 67%
“…Combination of folic acid demonstrably reduces this risk. A study in Psoriasis patients showed, that a dose of 20mg folic acid per week tended to decrease the efficacy of MTX (Chládek 2008). However, a study in rheumatoid arthritis showed that, administration of 5mg folic acid per week successfully reduced the hepatotoxicity without loss of efficacy (Morgan 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Apitherapy was available and inexpensive therapy in contrast with other therapeutic agents (23)(24)(25), but bee venom cost $5 only for each patient during the whole period of study. No recurrence of psoriatic lesions was detected during the follow-up observation period (6 months), and this was in agreement with Hegazi et al (10).…”
Section: Discussionmentioning
confidence: 99%